Polyaniline/graphene oxide/Zn-doped TiO2 nanocomposite coatings for the corrosion protection of carbon steel - Ladan, Magaji (Taylor & Francis, 2021)
This paper reports the synthesis of Polyaniline nanocomposites (PANI NCs) in the presence of graphene oxide (GO) and Zn-doped TiO2 nanoparticles by an in situ chemical polymerization method. The structure and morphology of the nanocomposites were analyzed by X-ray diffraction, Fourier transformed infrared spectroscopy, energy-dispersive X-ray analysis, field emission scanning electron microscopy and transmission electron microscopy. The corrosion resistance properties of PANI NCs were studied in 3.5% NaCl using electrochemical impedance spectroscopy and potentiodynamic polarization measurements. The coatings incorporated with PANI/GO/Zn-doped TiO2 NCs showed excellent corrosion resistance compared to those containing PANI/Zn-doped TiO2 and pure PANI. The corrosion current density decreased from 2.19 x 10(-6) A cm(-2) for the steel coated with butvar alone to 3.30 x 10(-12) A cm(-2) for the carbon steel coated with PANI/Zn-doped TiO2 NCs and to 4.32 x 10(-14) A cm(-2) for the carbon steel coated with PANI/GO/Zn-doped TiO2. The Tafel analysis shows that the corrosion rate of the carbon steel coated with PANI/GO/Zn-doped TiO2 NCs is lower compared to the coatings incorporated with PANI/Zn-doped TiO2 NCs and PANI, respectively. The EIS results show that the log |Z| value for the coatings prepared with PANI/Zn-doped TiO2 NCs and PANI/GO/Zn-doped TiO2 NCs is approximately 7.15 and 9.01, respectively, after 30 days of immersion in 3.5% NaCl solution. The excellent corrosion resistance properties of these coatings are likely due to the barrier effects, redox properties of PANI and increased surface area for the liberation of dopant with the incorporation of GO and Zn- doped TiO2 NPs.